Green and Wood Waste Biochar Based Soil Amendment to Mitigate Early Blight Stress in Tomato (Journal of Agriculture and Biology, 2025)
The use of available resources for the benefit of both environment and human beings comes under sustainable agriculture. Application of chemical fertilizers and pesticides is against the sustainable management of agricultural resources. Biochar acts as alternative to chemical pesticides and fertilizers by promoting the disease suppression and enhancing plant growth. Current study examines the effect of different biochar concentrations on growth enhancement of tomato plants and availability of essential nutrients like potassium and phosphorus both in the absence and presence of Alternaria solani infection. Soil was amended with green and wood waste biochar (GWB). Both biochar concentrations (3 and 6%) effectively minimized disease progress while enhancing plant growth. However, 6% GWB performed better. Both root and shoot length increased in soil amended with 6% GWB. Both disease incidence and severity reduced drastically in soil amended with 6% biochar. Nitrogen contents increased by 13.07% under stress conditions. The disease incidence was 100% in un-amended soil while it was reduced to just 20% in soil amended with 6% GWB. There was significant drop (6%) in disease severity in 6% GWB amended soil. In short, soil amendment with biochar proved effect strategy for mitigation of early blight in to tomato by stimulating plant growth parameters and minimizing disease incidence. Biochar application is crucial for sustainable agriculture.